Ultrasound-guided foam sclerotherapy versus four-layer compression only for treatment of chronic venous ulcers - Ahmed Sayed Ibrahim Issa; Riham Ibrahim; Michael Samuel Ayad; Momen Nagy; Azza M. Abdel Zaher; Ahmed M. Yassin (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background Chronic venous ulcers are prevalent, its incidence (1%) in the general population. Venous ulcers are quite a challenge for physicians to treat. Among the numerous pathological causes, venous hypertension remains the leading cause. This study aims to compare the safety, efficacy, short-term complications, factors affecting wound healing as well as pathological outcomes of ultrasound-guided foam sclerotherapy (UGFS) in conjunction with the four-layer compression bandage in the management of chronic venous ulcers. Methods Retrospective analysis of a hundred patients with chronic venous ulcers treated between December 2018 and December 2021. Two groups were studied: the control group, which received conventional compression, and the study group, which underwent injection sclerotherapy and conventional compression. Punch skin biopsies were taken from both groups before and after treatment to compare the histological effects of the two methods. Results Complete healing was achieved in 100% of the patients, with a shorter healing time in the study group (34.82 ± 4.7). Additionally, the degree of inflammation was significantly decreased but there was a higher local complication rate in the study group. Conclusions UGFS in conjunction with the compression bandage showed superior clinical and pathological results but, risk of complication was increased.